Effects of the TCF7L2 Genetic Variants on Anthropometric, Metabolic and Hormonal Parameters in Type 2 Diabetes Mellitus Patients who Following Diets Enriched with Nopal Tortilla and Wholegrain Bread - López-Ortiz, M. M.; Garay-Sevilla, M. E.; Tejero, M. E.; Perez-Luque, E. L. (Medical Science: Trends and Innovations Vol. 13, 2025)
Genetic polymorphisms in the human genome may contribute to phenotypic variation and genetic susceptibility to several diseases, with transcription factor 7-like 2 (TCF7L2) being one of the genes that is most consistently associated with T2DM across different studies and populations. The TCF7L2 genetic variants have shown differential effects on low-fat and high-fat diets in obese subjects. Nopal is a Mexican variety of cactus that is a traditional food and has been used in the treatment of diabetes. Its hypoglycaemic effect may be because of its soluble fibre (mucopolysaccharide) content. This study hypothesises that there are hormonal and metabolic differences in T2DM patients who carry different rs7903146 and rs12255372 TCF7L2 genotypes and consume diets containing either nopal or wholegrain fibre. This study analysed the effects of the vs7903146 and vs12255372 TCF7L2 variants on anthropometric, metabolic and hormonal parameters in type 2 diabetes mellitus patients who consumed fibre from either nopal tortilla or wholegrain bread for 8 weeks. Seventy-four patients who consumed an individualised isoenergetic diet that included nopal tortilla (Diet 1) and sixty-three patients with a diet that included wholegrain bread (Diet 2) were followed up. The T2DM patients received an individualised isoenergetic diet based on the 2004 American Diabetes Association (ADA) dietary recommendations. Anthropometric, metabolic and hormonal measures were collected at baseline and final intervention. The size effect and carry-over effect were estimated. To assess the interaction of genotype and diets, a general linear model repeated-measures analysis was used. Minor allele frequency of rs7903146T was 0·27 and for rs12255372T it was 0·13. IBM SPSS Statistics 19.0 software was used for all statistical analyses. At 8 weeks after Diet 1 intake, weight, BMI, waist and hip circumference decreased (P = 0·00015) in rs7903146CC and rs12255372GG genotypes. In particular, patients carrying the rs7903146CC and consuming Diet 1 showed a reduction in waist circumference of more than 2·5 cm compared with Diet 2 (P < 0·001). No significant interaction between rs7903146 or rs12255372 and diet was seen in this study. In conclusion, in the carriers of the vs7303146CC and vs12255372GG wild types, significant changes in all anthropometric measures were observed, and they had a better response to both diets. This result highlights the importance of considering patient genetic patterns when suggesting therapeutic diets. Differences in anthropometric, metabolic and hormonal responses should be considered when adapting and individualising diets of patients to better control T2DM.